Who is to blame? Perspectives of caregivers on barriers to accessing healthcare for the under-fives in Butere District, Western Kenya - Nyabola Lambert O; Laving Ahmed MR; Opwora Antony S; Olenja Joyce M (BMC, 2011)
Abstract Background Kenya, like many developing nations, continues to experience high childhood mortality in spite of the many efforts put in place by governments and international bodies to curb it. This study sought to investigate the barriers to accessing healthcare services for children aged less than five years in Butere District, a rural district experiencing high rates of mortality and morbidity despite having relatively better conditions for child survival. Methods Exit interviews were conducted among caregivers seeking healthcare for their children in mid 2007 in all the 6 public health facilities. Additionally, views from caregivers in the community, health workers and district health managers were sought through focus group discussions (FGDs) and key informant interviews (KIs). Results Three hundred and ninety-seven respondents were surveyed in exit interviews while 45 respondents participated in FGDs and KIs. Some practices by caregivers including early onset of child bearing, early supplementation, and utilization of traditional healers were thought to increase the risk of mortality and morbidity, although reported rates of mosquito net utilization and immunization coverage were high. The healthcare system posed barriers to access of healthcare for the under fives, through long waiting time, lack of drugs and poor services, incompetence and perceived poor attitudes of the health workers. FGDs also revealed wide-spread concerns and misconceptions about health care among the caregivers. Conclusion Caregivers' actions were thought to influence children's progression to illness or health while the healthcare delivery system posed recurrent barriers to the accessing of healthcare for the under-fives. Actions on both fronts are necessary to reduce childhood mortality.